Analisis Kalām Khabari dalam Kitab Lubāb al-Hadīṡ Karya Jalaluddin al-Suyuthi - Fajar, Ahmad; Luthfi, Taufik (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2022)
This study focuses on one of the works of Jalaluddin bin Kamaluddin al-Suyuthi, namely LubÄb al-Hadith which consists of forty chapters, each chapter contains ten HadÄ«á¹¡ with a total of four hundred HadÄ«á¹¡. This book contains about the virtues, prohibitions and prevention of the HadÄ«á¹¡ of the Prophet, the hadith Qudsi and Aá¹¡ar. The purpose of this study was to find out KalÄm Khabari and its various types contained in the book of LubÄb al-Hadith. The research method used in this research is the literature study method, which is a series of activities related to the methods of collecting library data, reading and taking notes, then processing research materials. Of the four hundred HadÄ«á¹¡ in forty chapters, Forty HadÄ«á¹¡ have been taken as samples in this study. So the results of the analysis of the LubÄb al-HadÄ«á¹¡ book found that 88% of KalÄm Khabar IbtidÄâ€™I and 12% of KalÄm Khabar á¹¬alabi were found, while KalÄm Khabar InkÄri was not found.